Reception Messages of Hate Speech among the Teenagers in the Global World: An Attempt to Gain the Good Quality of Labor Demands - Anis, M Y; Sari, L; Yuliarti, M S (KnE Social Sciences, 2018)
To gain the good labor demand, the government should care about the quality of its teenagers. The government must give the teenagers some labor/work to gain the maximum quality of moral ethics integrity and capability to work. In this case, some teenagers don’t care about the phenomena of hate speech. It becomes viral on YouTube when a Pakistani boy had been doing the hate speech to Indian girls. This research will elaborate the form of hate speech and the action of reception messages of hate speech among the teenagers from the global perspective. The result of this research was divided into two basics finding, they are: (1) the main form of hate speech, such as: the provocation for violence, the provocation for hatred, and the provocation for discrimination and (2) the reception messages of hate speech among the teenagers, such as: dominant, negotiable, and oppositional. When the teenagers still had a mutual understanding about the norms of Bhineka Tunggal Ika to avoid the hate speech, they will be the light future of nation to get the readiness of the best quality of labor demand in Indonesia. Keywords: reception messages, teenagers, hate speech, labor demand, global world